Electrochemical Copolymerization of Two Novel Polythiophene - Pan, Qiwei; Gao, Chuang; Pei, Meishan; Lai, Cunyuan (Asian Journal of Chemistry, 2012)
The copolymerization of poly-3-ethyl-3-({[6-(3-thienyl)hexyl]oxy}-methyl)oxetane (PTO) and poly[3-(hexyl methacrylate)] thiophene (PMT) was successfully achieved electrochemically in CH2Cl2 containing 25 % boron trifluoride diethyl etherate (by volume) as supporting electrolyte by direct anodic oxidation of the monomer mixtures on platinum or an optically transparent ITO electrode. As-formed copolymer own the advantages of good electrochemical behaviours and excellent ambient stability. The structure of the copolymer were investigated by UV-VIS, fluorescence spectra and thermal analysis, respectively. The fluorescence spectra indicate that PPOMT films are yellow-light emitters. Thermal analysis studies confirmed PPOMT has a good thermal stability.